Research Note: Polyembryony in Philippine Makapuno (Cocos nucifera L.) Hybrids - Tessie C. Nuñez; Edwin T. Ocoy (International Coconut Community Journal, 2008)
Polyembryony was found in five Philippine makapuno hybrids developed by the Visayas State University (VSU) namely: VMAC1, VMAC2, VMAC3, VMAC4 and VMAC5. Different numbers of multiple embryos in a nut, such as the most commonly encountered twins (2), the rare triplets (3) and quintuplets (5), were observed at very low frequencies of 0.7-10% per hybrid during some harvest periods. The multiple embryos were found clustered together under the ‘soft eye’ of the nut but they did not share any tissue. Among the hybrids, VMAC1 had the most frequent occurrence of polyembryony. Multiple embryos were encountered in VMAC1 in majority of the harvest periods. In the other four hybrids, polyembryony was very rarely observed. In vitro germination and development of the cultured polyembryos was almost synchronized. All polyembryos developed normally in vitro.